Perambatan Gravity Current dalam Skala Laboratorium sebagai Pemodelan Lahar Dingin dan Intrusi Air Laut - Wawan Eko Budianto; Imam Sucahyo; Tjipto Prastowo; Endah Rahmawati (Universitas Negeri Surabaya, 2013)
In the context of problem-based learning, gravity current experiment to model saltwater intrusion and œlahar dingin using a water tank available at the Laboratory of Earth Science in the Department of Physics, the State University of Surabaya is research breakthrough in physics education. This makes physics teaching meaningful as it is part of the introduction of disaster mitigation education to students in the department. The experiments were performed in two stages to determine the speed and depth of gravity current. In the first stage, a number of runs were conducted by varying density difference between saltwater and freshwater (1%, 3%, or 5%). The two fluids were filled in the tank at the total water depth of 10 cm or 20 cm. In the second stage, other runs were conducted using a water tank of the same length but twice narrower. The results show that the dimensionless speed is measured to be 0.44 ± 0.03, independent of the width of the tank. Relatively compared to the speed, the current depth is difficult to measure owing to the presence of mixing. However, experimental photos show that the current depth is best estimated to be 0.32-0.46 H, where H is the total depth